Comprehensive Transcriptomic Analysis Reveals Dysregulated Competing Endogenous RNA Network in Endocrine Resistant Breast Cancer Cells - Gao, Liang; Shen, Kunwei; Yin, Ni; Jiang, Min (Frontiers in Oncology, 2020)
Background: Tamoxifen and fulvestrant, both approved for endocrine therapy, have remarkably increased the prognosis of hormone receptor-positive breast cancer patients. However, acquired resistance to endocrine therapy greatly reduces its clinical efficacy. Accumulating evidence suggests a pivotal role of non-coding RNAs (ncRNAs) in breast cancer endocrine resistance, but the specific functions of ncRNAs in tamoxifen and fulvestrant resistance remain largely unknown. Methods: Microarray analysis was performed for endocrine therapy sensitive (MCF-7), tamoxifen-resistant (LCC2), and dual tamoxifen and fulvestrant-resistant (LCC9) breast cancer cells. Gene ontology and pathway analysis were conducted for functional prediction of the unannotated differentially expressed ncRNAs. Competing endogenous RNA regulatory networks were constructed. Results: We discovered a total of 3129 long non-coding RNAs (lncRNAs), 13556 circular RNAs (circRNAs), 132 microRNAs and 3358 mRNAs that were significantly differentially expressed. We constructed co-expression networks for lncRNA-mRNA, circRNA-mRNA, and microRNA-mRNA. In addition, we established lncRNA-microRNA-mRNA and circRNA-microRNA-mRNA regulatory networks to depict ncRNA crosstalk and transcriptomic regulation of endocrine resistance. Conclusions: Our study delineates a comprehensive profiling of ncRNAs in tamoxifen and fulvestrant resistant breast cancer cells, which enriches our understanding of endocrine resistance and sheds new light on identifying novel endocrine resistance biomarkers and potential therapeutic targets to overcome endocrine resistance.